Double degrees : research pathways, enabling cross disciplinarity and enhancing international competitiveness. - Moulton, Bruce; Iyer, Mahalinga; Shortis, Mark; Vuthaluru, Hari B.; Xing, Ke (Australian Learning and Teaching Council (ALTC), 2011)
The existing structures of the studied dual degrees enable students to complete 2 degrees, which would separately take seven years to complete, in five to five and a half years. The project examined the documented rationale for the shortening of the dual degree offering. In most cases, the stated explanation referred to RPL if a student undertakes a second degree, a student may apply to use learning from the first degree to gain credit in the second degree. The project found that there was a tendency for the amount and nature of the credit offered to students of dual degrees to differ from that offered to students of sequentially undertaken degrees. On the whole, dual degree students undertake less study than students who undertake the same two degrees sequentially. In some cases RPL-based explanations do not sufficiently explain the shortened structure of dual degrees. However, the project finds that, in reality, a large proportion of dual degrees are essentially two unrelated and poorly integrated courses placed side by side. Dual degrees might enable learning in two disciplines, but in most cases, dual degrees lack integrated cross-disciplinarity. [ALTC Website]